Pengaruh Profitabilitas, Leverage Dan Ukuran Perusahaan Terhadap Perataan Laba (Studi Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2018 - 2022) - Nastiti Rizky Shiyammurti; Non Sely Iklima (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study is to collect data and information and analyze related to profitability, leverage and company size on income smoothing in manufacturing companies listed on the Indonesia Stock Exchange for the period 2018 - 2022. The method used in this study is quantitative with a descriptive and associative approach. The sample used in this study was 67 companies through purposive sampling. The data used in this study are secondary data (indirect observation). The data analysis method uses panel data regression analysis (pooled data) with STATA software version 17. The results of the study show that partially shows that the profitability/ROA variable does not affect income smoothing, as well as leverage/DER does not affect income smoothing, while company size significantly affects income smoothing. Simultaneously, profitability, leverage and company size do not affect income smoothing in manufacturing companies listed on the Indonesia Stock Exchange (IDX). Because the significance level is > 0.05.